Penerapan Plot Linear terhadap Perkembangan Cerita dalam Film Dua Hati Biru Karya Sutradara Gina S. Noer - Jenny Fransiska; Dani Manesah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Film is a medium that functions as entertainment and an effective means of communication in conveying messages, stories and emotions to the audience. "Two Blue Hearts" by Gina S. Noer is a follow-up film to the story of Bima and Dara, a young couple who married at an early age because of a mistake. After four years apart since the birth of their son, Adam, Dara decided to return to Jakarta to be with Bima and Adam. Conflicts in their household arise again when Dara struggles to get closer to Adam, who does not yet recognize her as a mother. This research aims to determine the application of linear plot in the development of the story in the film "Dua Hati Biru". The theory used is the Linear Plot from Elizabeth Lutter. The results show that the use of a linear plot in Dua Hati Biru allows the audience to see the emotional transitions and dynamics of Bima and Dara's relationship clearly. This approach is effective in depicting character growth through a consistent passage of time, without relying on a back-and-forth plot.